2019
DOI: 10.3389/fmicb.2019.00529
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Succession and Response to Environmental Variables During Cow Manure and Corn Straw Composting

Abstract: In composting system, the composition of microbial communities is determined by the constant change in the physicochemical parameters. This study explored the dynamics of bacterial and fungal communities during cow manure and corn straw composting using high throughput sequencing technology. The relationships between physicochemical parameters and microbial community composition and abundance were also evaluated. The sequencing results revealed the major phyla included Proteobacteria, Bacteroidetes, Firmicutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
68
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 162 publications
(85 citation statements)
references
References 72 publications
(92 reference statements)
12
68
0
5
Order By: Relevance
“…was found to significantly correlate with the distribution of bacterial and fungal communities. This result was consistent with the report by Hu et al (2017) and Meng et al (2019). TOC is an essential nutrient for microbial growth and has been reported as an important factor affecting microbial community structure and metabolic type (Hu et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…was found to significantly correlate with the distribution of bacterial and fungal communities. This result was consistent with the report by Hu et al (2017) and Meng et al (2019). TOC is an essential nutrient for microbial growth and has been reported as an important factor affecting microbial community structure and metabolic type (Hu et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…This correlated with the nature and nutritional status of the CB system during the padding phases, thus suggesting bacterial species to be rolespecific and environment-sensitive. This result agrees with the previous studies by Ren et al (2016) and Meng et al (2019) who had reported similarity of bacterial diversity at both cooling and maturation stages during cow manure and corn/rice straw composting. CB, padded for 9 and 20 days, indicated the sharing of a high similarity of fungal community compositions.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations